Aplikasi Android Untuk Mengatur Switch Pada Perangkat Elektronik Nirkabel - Finanto, Menda, Bana Handaga, S.T.,M.T.,P.h.D (2015)
Android is a mobile operating system that delevoped at this time. It is an open source platform therefore developer easily make some modification or even a new applications. Android is applications used to manage switch on wireless electronic devices build for help people controling electronic services remotely by internet connection therefore user can control electronic devices. This application build used android studio a tools to make android applications and using Arduino IDE with internet connection to switch Services is power in on or off conditions. Internet connection used as a bridge of communications between android and arduino. Commands sent by android save in webserver and read by arduino for control switch and prototype, webserver also serves storing temperature information and status LEDs on the prototype.